All Days 2005
DOI: 10.2118/93952-ms
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Geologic Parameters on CO2 Storage in Deep Saline Aquifers

Abstract: The results of modeling injection into and long-term storage of CO2 in a deep saline aquifer with a commercial black-oil reservoir simulator are presented. Realistic CO2/water pVT properties covering all pressure, temperature and compositional conditions accounted for during the simulations have been used. The pressure and temperature in the aquifer is above the CO2 critical pressure and temperature giving rise to the existence of a two-phase fluid system of CO2 as a fluid and an aqueous phase containing disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The reservoir outer boundary cells were extended by multiplying their volume by 10 8 to simulate constant pressure boundary conditions (i.e. Dirichlet boundary conditions) . Porosity and permeability heterogeneity of the 10th SPE comparative solution project were used for each grid block to simulate a representative highly heterogeneous reservoir (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The reservoir outer boundary cells were extended by multiplying their volume by 10 8 to simulate constant pressure boundary conditions (i.e. Dirichlet boundary conditions) . Porosity and permeability heterogeneity of the 10th SPE comparative solution project were used for each grid block to simulate a representative highly heterogeneous reservoir (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Three dimensional simulations were performed using ECLIPSE 300 compositional software with CO 2 STORE option that can be used to calculate mutual solubility of CO 2 For simulation input data, Viking 2 relative permeability data were used for sandstone which have been taken from SPE paper (No. 99326) published by Bennion et al and Calmar were used for shale formation, the data have been obtained from Alberta geological survey website (AGS).…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Carbone capture and storage (CCS) is considered to be an important means of reducing the levels of CO 2 in the atmosphere [1]. CO 2 might be stored in an oil and gas reservoir, unmineable coal seam and deep saline aquifers [2,3]. Among these options, deep saline aquifers seem to be the most promising site for CO 2 storage, because they can potentially provide a large storage and they are widely spread throughout the world.…”
Section: Introductionmentioning
confidence: 99%
“…More recently it has been demonstrated that relative permeability hysteresis can increase the trapped/residual CO 2 saturation to S gr ≈ 0.4 in strongly water-wet reservoirs 16 . Various numerical simulations have now demonstrated that residual trapping can immobilize significant amounts of CO 2 relatively soon after the end of the injection period 16,17,18,19,20 .…”
Section: Propagation Of the Co 2 -Plume In A Slopingmentioning
confidence: 99%